The Impact of Dental Satisfaction Questionnaire (DSQ) and Word of Mouth on Patient Satisfaction Educational Dental and Oral Hospital - Reza Rahmadi Hasibuan (Telaah Bisnis, 2022)
The realization of satisfied patients provides benefits, including harmonious relationships with patients to hospitals, providing a good foundation for patient loyalty and recommending WOM. The general purpose of this survey is to find out the effect of satisfied patients through the dental satisfaction tools approach on the interest in recommending to others at the Unsoed Dental and Oral Education Hospital. This research is an analytic observational study with a cross sectional approach. With a total sample of 106 respondents, where the respondents were RSGMP patients. The research data collection method was carried out by collecting data directly in the field, namely through the questionnaire or questionnaire method where the questionnaire was a Dental Satisfaction Questionnaire, patient satisfaction variables and word of mouth variables. The results of the overall analysis concluded that dental patient satisfaction had a positive effect on RSGMP patient satisfaction and word of mouth had an effect on RSGMP patient satisfaction. Future research is expected to use interview or observation methods other than questionnaires as research instruments so that patient data can be obtained that are outside the sample criteria. Thus the data collected will be more varied.